Missed opportunities for human papillomavirus vaccination at office visits during which influenza vaccine was administered: An AAP pediatric research in office settings (PROS) national primary care research network study. Issue 33 (14th July 2020) - Kelly, Mary Kate; Grundmeier, Robert W.; Stephens-Shields, Alisa J.; Localio, Russell; Shone, Laura P.; Wright, Margaret; Steffes, Jennifer; Humiston, Sharon G.; Rand, Cynthia; Albertin, Christina; Breck, Abigail; Abney, Dianna E.; et al.
Abstract: Introduction: Little is known about missed opportunities (MOs) for HPV vaccination during primary care visits at which influenza vaccination is delivered. Methods: We extracted electronic health records for HPV vaccine-eligible 11-to-17-year-olds. We assessed the proportion of visits during which an influenza vaccine was given and an HPV vaccine was due, but not given (i.e., MOs). Results: Of 56, 135 eligible visits, 57.5% represented MOs for HPV vaccination. MOs were more common at visits where an initial versus subsequent HPV vaccine dose was due (68.6% vs. 31.3%) and for acute/chronic and nurse-only visits compared to preventive visits (74.0% and 80.2% vs. 36.7%). In a multivariable model, MOs were more likely for the initial HPV dose and for non-preventive visits, but did not vary by patient sex/age. Conclusions: HPV vaccine MOs were common during visits where influenza vaccine was administered. Increasing simultaneous administration of HPV and influenza vaccines could increase HPV vaccine coverage.